Out of Pace : Exploring Long-Term Issues with an Innovative Pacemaker - Zapanta, Conrad M.; Sinex, Deanna C.E; Pinkus, Rosa Lynn B. (McGraw-Hill's AccessEngineering., 2024)
It is 2005, and CardiaCraft Innovations Inc. is a leader in the research and development of innovative pacemakers. The pacemaker is used to electrically stimulate a damaged or weakened heart, and it has prolonged life for more than hundreds of thousands of individuals worldwide since its first implantation in 1958.1 Traditional pacemaker leads are straight; and because of the delicate anatomy of the heart, it is sometimes difficult for surgeons to implant the leads. The new Accufix J lead resembles a fishhook (or J shape) and is designed to enable surgeons to more easily feed it into both chambers of the heart. CardiaCraft Innovations Inc. claims this new device will revolutionize pacemaker implantation procedures. Through this case study, students will recognize the ethical and professional responsibilities of a newly hired bioengineer, a project manager, and an FDA official as they grapple with testing issues for an innovative medical device. This case will also explore the regulatory requirements of medical device applications, as well the technical and ethical issues associated with the submission, approval, and recall of medical devices.